The causality between rheumatoid arthritis and postural deformities: bidirectional Mendelian randomization study and mediation analysis - Zhao, Piqian; Chen, Zhe; Wen, Ya; Zhang, Hongtao; Wen, Liangyuan; Pei, Zijie (Frontiers in Immunology, 2024)
Background: To better understand the preventive or therapeutic clinical interventions that may be supported by the association between rheumatoid arthritis (RA) and postural deformities including hallux valgus, flat foot, and scoliosis, this study was conducted using Mendelian randomization (MR) analysis. It aimed to investigate whether RA is causally associated with postural deformities in European populations. Methods: Summary-level data on RA and postural deformities were obtained from the IEU OpenGWAS project and Finngen database, respectively. LDSC regression analysis was conducted to assess the genetic correlation between these diseases. The inverse variance weighting (IVW) method was employed as the primary approach for two-sample MR analyses to evaluate causality. Supplementary methods included MR-Egger, maximum likelihood, weighted median, and cML-MA. To test for potential horizontal pleiotropy, we performed the MR-Egger intercept test, cML-MA, and secondary analyses after excluding confounders. Additionally, mediation analyses were conducted using two-step MR. Results: The IVW method revealed RA to be causally associated with hallux valgus (OR 1.132, 95% CI 1.087-1.178, P < 0.001) and flat foot (OR 1.197, 95% CI 1.110-1.291, P < 0.001). Among postural deformities, hallux valgus was causally associated with flat foot (OR 1.823, 95% CI 1.569-2.119, P < 0.001) and scoliosis (OR 1.150, 95% CI 1.027-1.287, P < 0.05). No significant horizontal pleiotropy was detected. Moreover, mediation analyses indicated that hallux valgus mediates the effect of RA on flat foot (mediation effect 0.024, 95% CI 0.005-0.044, P < 0.05), with a mediation proportion of 41.31%. Conclusion: These findings indicate a potential causal association between genetically predicted RA and both hallux valgus and flat foot. Furthermore, hallux valgus serves as a mediator in the pathway from RA to flat foot. This underscores the importance of early screening and preventive treatment of foot deformities in RA patients. Further research is necessary to determine the applicability of these findings in non-European populations.